Does the Modification of Starting Gonadotropin Dose During ICSI Cycle Have Any Significant Impact on Cycle Outcome? - Enis Özkaya; Yavuz Şahin; Semra Kayatas Eser; Betul Albayrak; Oguzhan Bulduk; Ilhan Sanverdi; Tayfun Kutlu (Medical Network, 2017)
OBJECTIVE: The aim of this study was to figure out the impact of gonadotropin dose alteration requirements due to high response or unresponsiveness on intracytoplasmic sperm injection cycle outcomes in a standard group of patients. STUDY DESIGN: One hundred cycles with same gonadotropin dosage along the stimulation were compared with 100 cycles in which gonadotropin dose alterations were needed due to high response or unresponsiveness. Groups were compared in terms of age, body mass index, serum follicle stimulating hormone and estradiol levels, antral follicle count, gonadotropin dosage, duration of stimulation, endometrial thickness at trigger day, number of total, mature and immature oocytes and finally the clinical pregnancy rates. RESULTS: There were significant differences between groups with regard to gonadotropin starting dose, total gonadotropin dose, duration of stimulation, estradiol level at trigger day, number of total oocytes and metaphase 1 oocyte number. Clinical pregnancy rates were similar between groups. CONCLUSION: Dose alteration requirement along intracytoplasmic sperm injection cycle result in high number of total and metaphase 1 oocyte yields, higher starting gonadotropin and total gonadotropin dose, duration of stimulation and estradiol level at trigger day, however clinical pregnancy rates were similar between groups.